Behaviour of thermal expansion of (1-x)Pb(Ni1/3Nb2/3)O3–xPbTiO3 solid solutions - Bormanis, Karlis; Gorev, Mikhail G.; Flerov, Igor N.; Sternberg, Andris; Lace, Lelde; Ignatans, Reinis; Kalvane, Anna; Antonova, Maija (Estonian Academy Publishers, 2017)
The features of the dependence of the bulk coefficient of thermal expansion of the (1-x)Pb(Ni1/3Nb2/3)O3-xPbTiO3 solid solution studied in the series of x = 0-0.8 in the temperature range from 100 to 750 K are reported. The obtained data and observed anomalies of thermal expansion are compared with dielectric properties, heat capacity, and the phase diagram of concentration. The anomalous and lattice constituents of deformation and of the coefficient of thermal expansion are analysed and the data on deformation are used to estimate the Burns temperature and the mean square polarization of the samples found to decrease with the decrease of the PbTiO3 concentration.
The publication costs of this article were covered by the Estonian Academy of Sciences and the University of Tartu.
Keywords: ferroelectrics; relaxors; ceramics; solid solutions; thermal expansion; phase diagram; Research Subject Categories::NATURAL SCIENCES:Physics